(untitled) (Louisiana, US., 1997)
This study examines protein metabolism and growth in decapod crustaceans. Recognizing that successful commercial aquaculture of crustacean species is dependent on nutrition, the book focuses on the knowledge of crustacean nutritional requirements and factors affecting growth.
Dinh dưỡng và thức ăn thủy sản
Keywords: Shellfish culture,Crustacea; Feeding and feeds